Redesign, analysis, fabrication and testing of light weight wing for solar UAV : part 2 - Oh, Ying Qun (2014)
Unmanned Aerial Vehicles (UAVs) are aircrafts without a pilot on board and are employed in a variety of applications. The design of UAVs has been intensively researched over the past century and in the recent decades has evolved tremendously in terms of technology. The use of solar cells as a power source promises long endurance flights, while application of advanced materials such as carbon fibre dramatically reduces weight while maintaining structural integrity. The idea of a solar-powered UAV was proposed over 30 years ago and prototypes has already been tested and developed by both governmental and commercial agencies in US and UK. This collaborative project between NTU and DSO aims to build one of Singapore’s first such vehicles. The high altitude, long endurance (HALE) UAV will have an 18m wingspan, with solar panels acting as the upper wing skin. It will also be manufactured almost entirely out of carbon fibre. This report focuses on the structural design of the UAV specifically that of the wing assembly. It seeks to present innovative ideas to integrate avionics, propulsion and solar components with the wing structure. With the help of computer aided design and simulation software, dimensions and material usage of components were optimised for weight reduction and strength. Tests were also conducted on a 1-metre long spar specimen to verify theoretical calculations and determine their feasibility as the main load-bearing component. Structural joints between components, either permanent or removable, were also carefully thought out and modelled. Eventually, parts for a 3.2 metres test wing section was fabricated and assembled to demonstrate all structural features designed. In working towards building an airworthy prototype, further testing should be done on the test section. More load cases should also be examined, and material testing conducted, to ensure the UAV is versatile and structurally strong enough to survive unscathed under different flying manoeuvres and environmental conditions.